PENGARUH ENTERTAINMENT DAN INFORMATIVENESS TERHADAP KEPUTUSAN WISATAWAN BERKUNJUNG DI DELTA FISHING, PRASUNG, SIDOARJO - Heri Yanto; Mochamad Rizal Yulianto; Poppy Febriana (Kanal: Jurnal Ilmu Komunikasi, 2015)
This research aims to know the influence of entertainment and information towards decision of tourists in Delta Fishing Prasung, Sidoarjo. The type of research used assosiative research with quantiative approach. The sample in this study was 100 people. The technique data collection used questionnaire. The analysis technique used multiple linear regression analysis. Results of tests indicated that R amounted 0,768, it means that relations between free variables entertainment and information for decision of tourists in Delta Fishing were closely and strong. It is characterized by a value of R amounted 76.8%. The value of determination simultaneous (R square) as much as 0,664, it means that variable entertainment and information by 64,4 %, while the rest 35,6 % influenced by other variables that unobserved.